Dead space in acute respiratory distress syndrome - Ferluga, Massimo (Ann Transl Med, 2018)
Dead space is the portion of each tidal volume that does not take part in gas exchange and represents a good global index of the efficiency of the lung function. Dead space is not routinely measured in critical care practice, because the difficulties in in interpreting capnograms and the different methods of calculations. Different dead space indices can provide useful information in acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) patients, where changes in microvasculature are the main determinants for the increase in dead space and consequently a worsening of the outcome. Lung recruitment is a dynamic process that combines recruitment manoeuvres (RMs) with positive end expiratory pressure (PEEP) and low Vt to recruit collapsed alveoli. Dead space guided recruitment allows avoiding regional overdistension or reduction in cardiac output in critical care patients with ALI or ARDS. Different patterns of ventilation affect also CO(2) elimination; in fact, end-inspiratory pause prolongation reduces dead space, increasing respiratory system compliance; plateau pressure and consequently driving pressure increase accordingly. Dead space measurement is a reliable method that provides important clinical and prognostic information. Different capnographic indices can be useful to evaluate therapeutic interventions or setting mechanical ventilation.